Security and confidentiality of information under the application of cloud accounting compared to traditional accounting - Wali, Kawa; Karim Darwish, Bnar; Jabbar Abdulfattah , Shadan (Journal of Economics and Administrative Sciences, 2022)
Due to the continuous development and transition from manual to electronic accounting methods, users are now finding that accounting is simpler and more convenient. The recent shift in accounting to a faster technology has greatly improved its ability to serve users.The research aims at a number of objectives, including getting to know cloud accounting and software-based accounting, comparing the services of the top ten cloud accounting service providers around the world in terms of security and confidentiality to understand how they differ from traditional accounting, and understanding the current impact of cloud accounting using insights from accounting experts. Primary data were collected from accounting experts from various academics and professionals. A questionnaire form has been prepared for this purpose.Secondary data were collected from annual reports, books, international journals, the Internet, and other sources. The information collected was helpful in understanding the concepts and their effectiveness.According to the results, cloud accounting is a much-preferred option over traditional accounting for any organization looking to compete due to its many benefits, including accessibility, affordability, high security, and ease of use.Further study is needed, recent advances in accounting not only help small and medium-sized businesses (SMEs) improve their efficiency but also provide significant cost savings. In such circumstances, it is necessary to ascertain whether companies and financial institutions such as banks that promote these trends in their operations bring clear benefits, as well as how this may affect the business future of newly established companies and institutions. This paper provides insight into cloud accounting in small and medium-sized businesses from a managerial accounting perspective. Paper type: Research paper